If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 48 = 3c Reorder the terms: 48 + c = 3c Solving 48 + c = 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 48 + c + -3c = 3c + -3c Combine like terms: c + -3c = -2c 48 + -2c = 3c + -3c Combine like terms: 3c + -3c = 0 48 + -2c = 0 Add '-48' to each side of the equation. 48 + -48 + -2c = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -2c = 0 + -48 -2c = 0 + -48 Combine like terms: 0 + -48 = -48 -2c = -48 Divide each side by '-2'. c = 24 Simplifying c = 24
| 8n-16=5n+35 | | 18a^4b^6/2a^2b^3 | | 15=72+6x | | f(x+1)=6x^2+7x-6 | | s-5=7s-89 | | .3333x-6=.1429x+2 | | n^2-120=7*n | | -4.072=.8b | | 12+c=7 | | 7r+2= | | z+28+z+96=180 | | 5x+14=-3x-33 | | (a^2-5a)/(a^2-4a-5) | | 9x+8=-208 | | 1/15=1/19+1/c | | a+24=7a | | x^3-5x^2+4a=0 | | c+14=8c | | 30/155 | | 13=2(x-1)+1 | | 5(x+14)=-3x-33 | | 8=3(v-4)-8v | | c+14=c | | x^2-3x+1=2-3x | | (5b-9)=(8-2b) | | -4y-3(-7y-3)=-7-8(1-y) | | b^2-2=0 | | 2a+a+36=180 | | 7/8=21/n | | (6a-24)=3a | | x/3-4=-20 | | 5(x-14)=33 |